Distribution of the collagen IV isoforms in human Bruch’s membrane - Chen, L (Copyright 2003 British Journal of Ophthalmology, 2003)
Aims: To determine the distribution of the α1 to α6 chains of type IV collagen in Bruch’s membrane of the human posterior pole. Methods: Cryosections (10 μm) from 18 human eyes (20 months to 83 years old) were acid treated, blocked with 10% normal goat serum, incubated for 1 hour with monoclonal antibodies against type IV collagen isoform specific peptides at 1:75 dilution, and visualised with an ABC staining kit. Results: In Bruch’s membrane, the α1(IV) and α2(IV) chains were identified in retinal pigment epithelial (10/18 = 55%) and choriocapillaris basement membranes (18/18 = 100%); the α3(IV), α4(IV), and α5(IV) chains were also found in the retinal pigment epithelial basement membrane (13/18 = 72%). In the choroid, the α1(IV) and α2(IV) chains were detected in the blood vessels (18/18=100%). The α6(IV) chain was not identified in any sections. Conclusion: The heterogeneous distribution of α1–2(IV) and α3–5(IV) in Bruch’s membrane could give insights into the function of this structure in health, ageing, and diseases such as age related macular degeneration.